Beckett's Critical Complicity: Carnival, Contestation, and Tradition - Dina Sherzer (Studies in 20th & 21st Century Literature, 2014)
Review of Beckett's Critical Complicity: Carnival, Contestation, and Tradition, by Sylvie Debevec Henning
Keywords: Beckett& #x27; s Critical Complicity: Carnival Contestation and Tradition; Sylvie Debevec Henning; review; Samuel Beckett